GIS Approach for Spatial Data Visualization of Food Service Operator in Jakarta, Indonesia - Steven, Raymond; Nofriani, Allya Bertha; Malik, Samuel; Widaningrum, Dyah Lestari (Social Economics and Ecology International Journal, 2018)
The purpose of this study is to help the company to improve customer satisfaction about Red Bean restaurant locations. To improve the customer satisfaction in this study used Geographic Information System based on Thiessen polygon, buffer zone, and distribution facility analysis. The conclusions of this research are the company needs to improve restaurant location using Geographic Information System method.